Indoor Air Quality And Potential Health Risks In The Food Refinery In The Hot-Humid Tropics - Wong, Chiang Ann (2018)
Poor indoor air quality will lead to health problems thus reducing the productivity of a company. The most common health problem reported in the food industry is respiratory diseases which can be caused by poor air quality. This study aims to ascertain the indoor air quality and elemental concentrations of particulate matter in a food refinery. Potential risks were evaluated to recommend appropriate risk minimisation strategies. An indoor air quality monitoring was carried out at eight sampling locations within the premises of a food refinery. Nine parameters including physical, chemical, biological parameters and the ventilation indicator were monitored using the methods of real time monitoring, gravimetric and plate count. The results were evaluated against standards. Particulate matter 10 micron (PM10) was analysed for elemental concentrations using ICP-OES and health risks were determined. Air temperature, air velocity, carbon dioxide (CO2) and PM10 at seven sampling locations exceeded the standards due to influence of outdoor air temperature, mechanical fan and natural wind, insufficient ventilation rate, air-conditioner settings, machinery emissions and food dust emissions. For elemental concentrations in particulate matter, Ca, Mg, Ni, Zn and Se were detected. The sources of detected elements could be from the food and human activities including traffic and industrial pollution. For the parameters that exceeded the standard, health impacts might stem from the exposure to high air temperature and high concentration of particulate matter. For potential health risk, Ni was found to pose both non-carcinogenic and carcinogenic health risk to the building occupants. Different risk minimisation strategies were addressed which covered the responsibility of management of company and workers.